THE RELATIONSHIP BETWEEN SELF-ESTEEM AND SUBJECTIVE WELL-BEING (In case of NUM students) - G.Uyanga; N.Sonintamir; B.Nomundari, (Journal of Business and Innovation (Бизнес & Инноваци), 2024)
We have examined the relationship between subjective well-being and self-esteem. A total of 237 students aged between 18-19 university students in Mongolia participated in the current study. This age is an important period in a person’s life. They go through many challenging changes in terms of biology and psychology. They responded to the Rosenberg’ the adolescent and self-esteem scale. Exploratory factor analysis of scales was analyzed via SPSS 23.0 software. The result suggested that the there’s strong correlation between high self-esteem and positive affect. When students’ self-esteem lowers their positive affect declines. There’s slight difference the correlation between high and low self-esteem with life satisfaction. Students with high self-esteem perceive life as good and happy. Even though their self-esteem low they still tend to be happy.